ChemInform Abstract: A Modular and Scalable One‐Pot Synthesis of Polysubstituted Furans. Issue 1 (3rd January 2013) - Fournier, Jeremy; Arseniyadis, Stellios; Cossy, Janine
Abstract This one‐pot, four‐step sequence consists of Pd‐catalyzed decarboxylative allylic alkylation followed by Cope rearrangement, nucleophilic addition and dehydration.